Benefits of stretching for lumbar mobility disorders at Murni Teguh Hospital Medan - Tuty Swarni Sinaga; Jhon Roby Purba (CV. AFDIFAL MAJU BERKAH, 2026)
The waist is the most important area as a point of strength for both legs located in the arrangement of the lumbar vertebra column 1 to the lumbar verbra column 5. The large lumbar vertebra is the structure that receives the most load on the sceletal system and is wider vertically in the front than in the back. Posture while working has a large influence on the accumulation of lower back muscle injuries, biomechanical factors related to static work postures and also standing and sitting postures. The research method used was pre-test and post-test, with a sample of 10 women and men aged around 25 to 55 years, and using the MAS (Modified Ashworth Scale) spasm scale measuring tool with a duration of 10-15 minutes of stretching exercise, and a waist stretching time of 4-5 weeks. and it was found that there was a significant influence carried out by physiotherapists, namely stretching exercises in the waist area with the aim of maintaining waist muscle strength and relaxing the waist.